2007
DOI: 10.1038/sj.onc.1210371
|View full text |Cite
|
Sign up to set email alerts
|

Anti-idiotype antibodies in cancer treatment

Abstract: As a cancer immunotherapy tool, idiotypes (Ids) have been used in different ways over the last three decades, depending on the actual human tumor cell target. It all started with passive, monoclonal, anti-Id antibody treatment of B-cell lymphoma, a setting in which results were tantalizing, but logistics unsustainable. It then moved toward the development of anti-Id vaccines for the treatment of the same tumors, a setting in which we have recently provided the first formal proof of principle of clinical benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 70 publications
0
43
0
Order By: Relevance
“…The use of anti-idiotype antibody in the control of K88 Eschershia coli (Jaradat et al, 2010), Edwardsiella tarda (Qin et al, 2010), hepatitis B (Yildrim et al, 2004, HIV-1 (Mader and Kunert, 2012), prion diseases (Venturini et al, 2009), cancer (Cerio et al, 2007) and atherosclerosis (Brito et al, 2012) were reported before.…”
Section: Discussionmentioning
confidence: 92%
“…The use of anti-idiotype antibody in the control of K88 Eschershia coli (Jaradat et al, 2010), Edwardsiella tarda (Qin et al, 2010), hepatitis B (Yildrim et al, 2004, HIV-1 (Mader and Kunert, 2012), prion diseases (Venturini et al, 2009), cancer (Cerio et al, 2007) and atherosclerosis (Brito et al, 2012) were reported before.…”
Section: Discussionmentioning
confidence: 92%
“…An alternative, although not exclusive possibility is represented by the induction of anti-idiotypic antibodies, i.e. antibodies specific for the variable region of the administered TA-specific mAb [50,51]. In some cases, these anti-idiotypic antibodies may mimic the TA recognized by the original TA-specific mAb and function as a surrogate antigen [50,51].…”
Section: Molecular Mechanisms Underlying the Therapeutic Efficacmentioning
confidence: 99%
“…In clinical trials, including patients with ovarian carcinoma, colorectal carcinoma or malignant melanoma, anti-Id-specific humoral and/or cellular responses following immunization were associated with a better survival rate without toxicity, but with modest objective responses. Available results of treatment of breast cancer patients with anti-Id mAbs are still very preliminary and conclusions go no further than the mere biologic proof of principle [20]. …”
Section: Introductionmentioning
confidence: 99%